PENGARUH STORE IMAGE DAN STORE THEATRICS TERHADAP PURCHASE INTENTION PADA TOKO AZWA PERFUME PEKANBARU - Erni Susianti; Endang Sutrisna (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This research was conducted at Store Azwa Perfume Pekanbaru which is located at Tenku Umar Street No 79, Rintis, LimaPuluh Kota Pekanbaru. The purpose of this research is to find out Store Image and Store Theatrics to purchase intention at Toko Azwa Perfume Pekanbaru. Store Image and Store Theatrics (X1X2) as independent variables while purchase intention as dependent variable (Y). The problem in this research is not reaching the target in 2013. The samples are taken from 100 respondents and the technique used is Accidental Sampling then tested using SPSS statistics.Hypothesis testing using simple linear analysis method and multiple linear anaisis. From the results of tests conducted show that store image and theatrics store have a positive and significant impact on purchase intention at Azwa Perfume Store Pekanbaru. With R2 value of 0.619. This shows that store image and theatrics store give effect of 61,9% to purchase intention at Store Azwa Perfume Pekanbaru, while the rest 38,1% influenced by other variable that are not examined in this research.Keywords : Store Image, Store Theatrics and Purchase Intention